PENGARUH PENGGUNAAN TEKNIK COPY THE MASTER TERHADAP KEMAMPUAN MENULIS CERPEN SISWA KELAS X SMA NEGERI 1 SUNGAI TARAB - Putri, Vivi Anggela; Asri, Yasnur; Zulfitriyani, Zulfitriyani (Pendidikan Bahasa Indonesia, 2014)
This study aimed to describe: first, the ability to write short stories at student of class X SMA Negeri 1 Sungai Tarab in terms of studentâs ability to develop plot, setting, and characterization. Second, the influence of using the copy master technique to the ability of writing the short stories for student of class X SMA Negeri 1 Sungai Tarab in terms of studentâs ability to develop plot, setting, and characterization. This research is a quantitative study with experimental methods. Sample size was 20 respondents, taken with purposive sampling technique. The data of this study is the scores of the ability to write short stories at class X SMA Negeri 1 Sungai Tarab before and after using the copy master techniques. The data is analyzed and then conducted the t-test to determine the influence of using the copy master technique to the ability of writing the short stories for student of class X SMA Negeri 1 Sungai Tarab. Based on the research results, it was concluded the following three points. First, the ability to write short stories at class X SMA Negeri 1 Sungai Tarab before using the technique of the copies master are on Good (B) qualification with an average (77.45). Second, the ability to write short stories at class X SMA Negeri 1 Sungai Tarab after using the copy master techniques are on the Good (B) qualification with an average (85.7). Third, there is a significant influence in the using of the copy master techniques in teaching the short story writing at class X SMA Negeri 1 Sungai Tarab with toutput (2,34) > ttab1e (1.73). In other words, H1 is accepted and Ho is rejected. Thus, the copy master technique is ideal to be used in learning of writing the short stories.